2014
DOI: 10.1155/2014/867852
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Cognitive Function and Hearing Impairment in Older Adults: A Preliminary Study

Abstract: Background. Previous research has found that hearing loss is associated with poorer cognitive function. The question is that when a hearing impairment is being compensated for by appropriately fitted monaural hearing aids, special precautions are still needed when screening cognitive function in older adults. Objective. This research examined cognitive function in elderly hearing aid users who used monaural hearing aids and whether the presence of a hearing impairment should be accounted for when screening cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
0
43
1
2
Order By: Relevance
“…Review of the literature led to 6 possible explanations that may further support the findings in our study for elderly patients following treatment of their hearing impairment especially for short-term memory, overall cognitive function and depression. These include the following: (1) reducing social isolation and improving depression symptoms could explain some early effects [Acar et al, 2011;Boi et al, 2012]; (2) electrical stimuli may allow the preservation of the function and 3-dimensional structure of the peripheral and central synapses [Kumar and Foster, 2007;Ryugo et al, 2005;Wong et al, 2009Wong et al, , 2014; (3) auditory rehabilitation can counteract negative neuroplasticity processes [Lazard et al, 2010[Lazard et al, , 2011[Lazard et al, , 2013; (4) the effect of auditory/speech training may positively influence working memory and learning abilities; (5) improvements in self-motivation, self-esteem or self-confidence after rehabilitative procedures occur resulting in a positive effect on cognitive skills, and (6) a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature led to 6 possible explanations that may further support the findings in our study for elderly patients following treatment of their hearing impairment especially for short-term memory, overall cognitive function and depression. These include the following: (1) reducing social isolation and improving depression symptoms could explain some early effects [Acar et al, 2011;Boi et al, 2012]; (2) electrical stimuli may allow the preservation of the function and 3-dimensional structure of the peripheral and central synapses [Kumar and Foster, 2007;Ryugo et al, 2005;Wong et al, 2009Wong et al, , 2014; (3) auditory rehabilitation can counteract negative neuroplasticity processes [Lazard et al, 2010[Lazard et al, , 2011[Lazard et al, , 2013; (4) the effect of auditory/speech training may positively influence working memory and learning abilities; (5) improvements in self-motivation, self-esteem or self-confidence after rehabilitative procedures occur resulting in a positive effect on cognitive skills, and (6) a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Wong et al conducted a prospective study in 34 older adults and found that, despite appropriately fitted hearing aids, they had significant benefits only for improve sensitivity to sound and speech understanding. However, cognitive decline was still significant and not fully compensated by hearing aids[21]. …”
Section: Hearing Lossmentioning
confidence: 99%
“…In short, hearing loss and vestibular disorders could be early symptoms of a cognitive decline and, therefore, effects , not causes. This aspect has been amply cited in relation to the preclinical diagnosis of dementias [Wong et al, 2014], as seen for vision and the eye [Chang et al, 2014;Kerbage et al, 2013]. So, hearing loss can be seen both as a screening method (to test for cognitive decline or dementia) and as a modifiable risk factor for preventing cognitive impairment [Gurgel et al, 2014;Lin et al, 2011;Parham et al, 2013].…”
Section: Issues and Perspectivesmentioning
confidence: 99%